2021
DOI: 10.1111/1756-185x.14160
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR‐98‐5p expression induces interleukin‐6 expression in rheumatoid fibroblast‐like synoviocytes

Abstract: Aim The increased level of interleukin‐6 (IL‐6) plays a significant role in the pathogenesis of rheumatoid arthritis (RA). Specific blockade of IL‐6 or its receptor has been used successfully in treating RA. MicroRNAs can regulate gene expression and act as regulators of target genes. Manipulation of specific microRNAs provides a novel therapeutic strategy for treating/preventing diseases. This study explored the role of miR‐98‐5p in the regulation of IL‐6 expression in rheumatoid fibroblast‐like synoviocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Apoptosis was also inhibited by reducing protein kinase 1 (DAPK1), Bcell lymphoma/leukemia-2 (Bcl-2)-associated X protein (BAX), and cleaved caspase-3 levels (59). In addition, miR-98-5p can negatively regulate the expression of IL-6 and is related to the inflammatory response (60). Moreover, tumor-related studies have also confirmed that miR-98-5p regulates cell proliferation and apoptosis (61).…”
Section: Discussionmentioning
confidence: 98%
“…Apoptosis was also inhibited by reducing protein kinase 1 (DAPK1), Bcell lymphoma/leukemia-2 (Bcl-2)-associated X protein (BAX), and cleaved caspase-3 levels (59). In addition, miR-98-5p can negatively regulate the expression of IL-6 and is related to the inflammatory response (60). Moreover, tumor-related studies have also confirmed that miR-98-5p regulates cell proliferation and apoptosis (61).…”
Section: Discussionmentioning
confidence: 98%
“…Regarding miR-98-5p, Wang et al reported that this miRNA negatively modulates IL-6 expression in rheumatoid fibroblast-like synoviocytes, serving as a potential regulator of the inflammatory process. Therefore, they proposed that the manipulation of miR-98-5 could be a potential clinical intervention, serving as an inhibitor of IL-6 expression in rheumatoid arthritis [ 87 ]. On the other hand, this miRNA also targets IL-10, which is an anti-inflammatory cytokine and plays an important role in maintaining intestinal homeostasis and the mucosal barrier.…”
Section: Sars-cov-2-related Mirnas Deregulation Impact On Cancer Pati...mentioning
confidence: 99%